Diversity, traditional uses and conservation status of Zingiberaceae in Udorn Thani Province, Thailand - Piyaporn Saensouk; Surapon Saensouk (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk P, Saensouk S. 2021. Diversity, traditional uses and conservation status of Zingiberaceae in Udorn Thani Province, Thailand. Biodiversitas 22: 3083-3097. Southeast Asia is recognized as the center of Zingiberaceae distribution with Thailand is among the important regions. Nonetheless, a comprehensive study in a regional context that investigates the biological aspects of the family is lacking. This study aimed to determine the diversity, distribution, ecology, conservation status, and traditional uses of the family Zingiberaceae in Udorn Thani Province, northeastern Thailand. In total, three tribes, nine genera, 47 species of Zingiberaceae were identified during a botanical survey between January and December 2020 in Udorn Thani. Curcuma and Kempferia were the most diverse genera with nine and eight species, respectively, followed by Zingiber as the third most diverse genus with seven species and Alpinia as the fourth most diverse genus with six species. While the genera Etlingera and Hedychium were the least diverse with each containing just one species. For all Zingiberaceae species, the flowering period was found between March and September, while the fruiting period was found between May and October. Zingiberaceae was found with the greatest frequency in five ecosystem types, namely cultivated areas, deciduous dipterocarp forest, mixed deciduous forest, dry evergreen forest and river basin. Twenty-one species were reported as rare species in research area, i.e. Boesenbergia baimaii, B. isanensis, Kaempferia picheansoonthonii, and K. udonensis. It was revealed that the traditional uses of many Zingiberaceae species from villagers in Udorn Thani Province were most frequently used for medicine, food, ornamentals, rituals, spices, perfume and cosmetics. Rhizomes, roots, pseudostems, young inflorescences, inflorescences, young leaves, leaves and fruits were the parts of this plant used.